Cutaneous vasculitis; An algorithmic approach to diagnosis - Alpsoy, Erkan (Frontiers in Medicine, 2022)
Vasculitides, characterized by inflammation and damage of blood vessels, encompass a broad spectrum of diseases. They can occur with different pathophysiological mechanisms and have a rich clinical heterogeneity depending on the vessel diameters they affect. Vasculitides may also present with a broad spectrum of severity, ranging from a mild self-limiting to a potentially life-threatening disease. The high prevalence of skin involvement in vasculitis, visible character and, finally, the easy accessibility of the skin for both physical examination and biopsy offers important advantages for prompt disease recognition and diagnosis. Thus, dermatologists are privileged to diagnose the disease earlier and more effectively than any other discipline. As a consequence, a detailed clinical and histopathological evaluation of the skin is one of the most critical steps in diagnosing vasculitis. Besides obtaining a good medical history, laboratory and radiological evaluation methods are used in the diagnosis. In this review, a practical and algorithmic approach is aimed to assist in the diagnosis of vasculitis. However, this approach should not be seen as strict rules. This stepwise algorithmic diagnostic approach for vasculitis was developed by combining the current literature knowledge and the author's experience in this field to provide a rational framework for selecting the most appropriate among various diagnostic approaches.